Growth performance and mineral composition of the white shrimp Penaeus vannamei and the sea grape Caulerpa lentillifera in a co‐culture system. (22nd September 2022) - Omont, Alexia; Peña‐Rodríguez, Alberto; Terauchi, Shuma; Matsui, Ayako; Magallón‐Barajas, Francisco; Torres‐Ochoa, Erika; Endo, Masato
Abstract: Integrated systems have been proposed as a sustainable solution to minimize the environmental impact of shrimp intensive aquaculture practices. The increasing demand for seafood is largely attributed to a growing need for healthy food recommended in a human balanced diet, but information on the nutritional quality of the resulting products is still scarce. In this study, a co‐culture system (CO) of white shrimp Penaeus vannamei and sea grape Caulerpa lentillifera were evaluated in 50‐L tanks during 28‐days. Water nutrients and mineral composition were measured every 4 days using spectrophotometry and ICP‐AES, respectively. At the end of the experiment, growth performance of shrimp and seaweed, proximal composition of shrimp and mineral composition of shrimp and seaweed were evaluated. Shrimps in CO revealed a better final weight (15.4 ± 0.02 g) and lower feed conversion rate (1.4) compared with monoculture system (13.5 ± 0.4 g; 1.9). C. lentillifera, in the CO system, bioremediate 64.0% of ammonium, 62.5% of nitrite, 82.4% of nitrate and 53.3% of phosphate. Regarding minerals, there were less P, Ca, Mn, Fe and Zn in CO water than in shrimp monoculture water . Concerning products' compositions, in CO, sea grapes had higher protein content and shrimps revealed higher lipid content in muscle, lower whole‐body cholesterol, higher concentrations in Fe (+70.2%), Zn (+14.8%), Co (+62.7%), Mn (+49.9%) and lower concentrations in Na (−13.7%). Thus, cultivating P. vannamei and C. lentillifera in a co‐culture system led to an increase the nutritional value of aquaculture products and to improve their interest in a human healthy diet.